Rehabilitacijski protokoli po delni odstranitvi meniskusa - Divjak, Mojca (Šport (Ljubljana), 2010)
Knee joint is one of the most frequently damaged joints, due to its anatomic structure, great exposure to the different external influences and also due to its big functional requirements. In most cases, knee injuries encounter the injuries of internal soft structures, particularly meniscal injuries. The purpose of this review of literature is to introduce different rehabilitation approaches, when treating knee joint after partial removal of meniscus, based on review of scientific literature. On the basis of the written keywords many articles were found. Nine of them were used for writing this paper. The articles studied the effectiveness of exercising at home, supervised physiotherapy, electrotherapy (ES), EMG - biofeedback and the effectiveness of early and subsequent treatment. Studies have shown different effectiveness of selected rehabilitation protocols. Physiotherapy resulted to be successful in reducing the symptoms and unsuccessful when returning to daily functional activities.
Keywords: fizioterapija; koleno; kolenski sklep; meniskus; poškodbe; rehabilitacija